Mortality and immortality - Matthew D. Rablen; Andrew J. Oswald (Institute for the Study of Labor (IZA), 2007)
It has been known for centuries that the rich and famous have longer lives than the poor and ordinary. Causality, however, remains trenchantly debated. The ideal experiment would be one in which status and money could somehow be dropped upon a sub-sample of individuals while those in a control group received neither. This paper attempts to formulate a test in that spirit. It collects 19th-century birth data on science Nobel Prize winners and nominees. Using a variety of corrections for potential biases, the paper concludes that winning the Nobel Prize, rather than merely being nominated, is associated with between 1 and 2 years of extra longevity. Greater wealth, as measured by the real value of the Prize, does not seem to affect lifespan.
urn:nbn:de:101:1-20080425369
Keywords: 330; Gesundheit; Sterblichkeit; Sozialer Status; Reichtum; Nobelpreis; Wissenschaftler; Schätzung; Welt